Actual Concept of Professional Creativity: Theoretical and Psychological Aspect - Alexander Nabochuk (Проблеми сучасної психології, 2023)
The aim of our article is to analyze the problem of professional creativity from the point of view of the acquisition of professional competence by specialists in the process of their professional formation and personal growth; to single out a content and semantic components of professional creativity; to present the author’s theoretical model of professional creativity. Methods of the research. The following theoretical methods of the research were used to solve the tasks formulated in the article: a categorical method, structural and functional methods, the methods of the analysis, systematization, modeling, generalization. The results of the research. We proved, that the actual concept of professional creativity can be presented in the form of a rather simplified model, which includes the following components: personal, its socio-biological, psycho-physiological, psychological and pedagogical, acmeological, axiological and intellectual characteristics; professional problems, professional tasks, situations, their varieties (semi-creative, creative, etc.), theories and methodology of problem formulation and consideration of various approaches to its solution; professional activity, environment, social environment, psychological conditions for adaptation and professional creativity, aspects of social interaction and influence on the effectiveness of the creative process; the creative process itself, its theoretical and methodological foundations of professional creativity. Conclusions. The study of professional creativity was carried out in the paradigm of two directions. The first one was related to the question of whether the level of formation of professional creativity depends on intelligence, and whether the subject is oriented towards the formation of cognitive processes in the connection with the acquired professional creativity. The second direction has the aim at finding out what the psychological features and aspects of professional creativity are. Among the latter, the attention of the individual, his/her personal and motivational characteristics was singled out.